Mejora del proceso de abastecimiento del taller de mecánica automotriz autoservicios Untiveros S. A. C. - Huaman Giribaldi, Franco Enrique (2023)
The present research work carries out a study to improve supply process of auto-parts in Autoservicios Untiveros SAC’s Auto Repair Centre based on Industrial Engineer’s techniques like reorder point, business process reengineering and simulation process to improve problems related stock shortage. It was also proposed alliance between American company called Mighty to supply auto-parts to preventive maintenance. The issue mainly is no count with suitable purchase process for auto parts to preventive maintenance, it causes break of stock it reduces effectiveness and efficiency level. The research techniques were observation (visits to Autoservicios Untiveros, historical data recollection), and general manager interview. The results have been modeling from current scene that does not count with safety stock policy. With Arena software a simulation in stable state was carried out with simulation duration or replication length of one year and warm up period of one month to both scenarios and the result was a drop of 30% stock shortage regarding improvement. This project focus on improves purchase process, it is commonly present breakdown it relies on stock availability, it represents loss of time and money finding out auto parts considering that the company don’t have replenishment inventory policy. Currently the purchase policies are that we buy when we need (just in time) and they have a small stock of some auto parts. The last chapter called economic and financial evaluation of solution carried out a variation economic and financial in relation pre-improvement and pro-improvement. The NPV financial obtained was S/28 310, a IRR obtained was 17%, a cost-benefit ratio 1,24, and payback period 4 years 4 months 10 days. The NPV was calculated to 5 years with cost of equity 25,38%. The cost of equity was calculated using Cappital Asset Pricing Model (CAPM).